Filtration of sugar-beet pulp pectin extract and flow properties of pectin solutions - Arslan, N; Kar, F (Elsevier Sci Ltd, 1998)
Sugar-beet pulp pectin extract was vacuum filtered at 25 degrees C and different filtration pressures (0.20 x 10(5), 0.33 x 10(5) and 0.47 x 10(5) Pa). The measurement of the average specific cake resistance was discussed The specific cake resistance was dependent on the filtration pressure. The cake compressibility coefficient at 25 degrees C was calculated as 0.389. The correlation between the pressure drop and the average specific cake resistance showed that sugar-beer pectin forms a compressible filter cake. By using kieselguhr asa filter aid to increase the filtration efficiency, the effects of varying the precoating amount and the filter aid dose on the average specific cake resistance of cake Lit a constant pressure filtration were studied. The effects of temperature and concentration on the viscosity of pectin solutions were examined at six different temperatures between 20 and 70 degrees C and four concentration levels between 0.005 and 0.020 kg l(-1). The activation energy for viscous flow was in the range 6.69-13.46 kJ mol(-1). Equations describing the combined effects of temperature and concentration on the viscosity are given. (C) 1998 Elsevier Science Limited. All rights reserved.
Keywords: Viscosity; Peel